Implantación del sistema de contabilidad comercial en la empresa Prohogar del cantón Palanda provincia Zamora Chinchipe periodo julio – septiembre del 2013 - Romero León, Mileny del Cisne (2015)
The thesisentitled "IMPLEMENTATION OF BUSINESSACCOUNTINGSYSTEMIN THE COMPANYOFCANTONPROHOGARPALANDAPROVINCEZAMORACHINCHIPEPERIODJULY -SEPTEMBER2013", has beendeveloped based onthat establishedthe rules of theNational University ofLoja,asa prerequisitetochoosethe title ofEngineerin Accounting and AuditingCPAalsobeen consideredthat firmsshould havestructuredthe entire accountingprocess formaximum efficiency, so it was proposedto implementtheaccountingcompanyPROHOGAR, in order toobtainfinancialresults on theeconomic movementofthe companyand alsoto be usefulfor the ownerand thuscontributesignificantlyin the accounting fieldto improvecontrol proceduresand optimizethe useof human, economic and financial resourcesincompany. Once theaccountingPROHOGARhasmanaged to meetthe goals outlined inthe research project, whichbegan withthe inventoryidentifyingpropertyrights, obligations and liabilities that the enterprise holds, then theaccounting processwas developed withthe different movementseconomicgenerated, they are backedwith the respectivesupporting documentation; economic activitydevelopedbefore beingplacedin the respective accountsand thusget thefinancial statements andmaydetermine the futureeconomic and financial situationof the company, also based oneconomic performance. Finally, we haveapplieddifferent accountingrecords according tothe economic activity ofthe company,theyserve toensure economic andfinancial transactions, so the person in chargeof the accountingpartis recommended to continueusingthe reportson the developmentaccounting, theyserve to ensurethatthefinancial reportsobtained